Pengaruh Motivasi Pada Minat Mahasiswa Non Akuntansi Program Reguler Mengikuti Pendidikan Profesi Akuntansi - Jeniari, Aven Maria; Dwija Putri, I.G.A.M Asri (E-Jurnal Akuntansi; Vol 28 No 3 (2019), 2019)
This study aims to determine the effect of social motivation, career motivation, quality motivation, economic motivation and degree motivation on the interest of non accounting students to take part in the accounting profession education program (PPAk). This research was conducted at the Faculty of Economics and Business, Udayana University, in the non-accounting S1 regular program students, using questionnaire techniques as data collection. The number of respondents in this study was 169 people. The analysis technique used is multiple linear analysis techniques. Based on the results of the research analysis, it is known that social motivation, career motivation, degree motivation, economic motivation, and quality motivation influence the interest of non accounting students to take part in Accounting Professional Education. Knowledge . Keywords : Social motivation, career motivation, degree motivation, economic motivation, quality motivation, interest in joining PPAk.